Containing Prescription Drug Costs at a Resource-Limited, Student-Run Clinic for the Uninsured - Batra, Jaya; Xu, Haoming; Rifkin, Robert A; Wang, Ann; Atteberry, Preston; Thomas, David C; Meah, Yasmin S (Journal of Student-Run Clinics, 2017)
Prescription drug coverage and reduced medication copayments have been shown to increase medication adherence, improve health care outcomes, and reduce racial and ethnic outcome disparities. This is especially true for uninsured patients who face greater obstacles and cost-barriers in obtaining medications than their insured counterparts. For this reason, some free clinics, including our own, provide medications to patients at no out-of-pocket cost. However, the price of supplying pharmaceuticals and medical supplies at reduced or no cost is a significant financial burden to free clinics, particularly those committed to providing care to the chronically ill, a population whose monthly drug costs can be steep. In this article, we present our free clinic’s evidence-based, value-conscious approach to providing patients with prescription medications at no charge, and evaluate the cost-savings of this operation. Specifically, we highlight the following three strategies and the associated annual savings: implementation of an evidence-based formulary with drug costs available at the point-of-care; the use of Patient Drug Assistance Programs to obtain expensive, off-formulary medications; and utilization of wholesale vendors to obtain blood glucose testing supplies. We present the opportunities, limitations, and lessons learned from this ongoing effort for free clinics to optimize their own drug and medical supply coverage programs.